Escuela primaria Mihama Utase, Chiba. 2003-2006 (2007)
Por <Kazuhiro Kojima + Kazuko Akamatsu / CAt>
Keywords: KOJIMA, KAZUHIRO; AKAMATSU, KAZUKO; JAPON; KANTO; CHIBA; ARQUITECTURA EDUCACIONAL; ESCUELAS PRIMARIAS; CONSTRUCCION; HORMIGON; CERRAMIENTOS; VIDRIO